1992
DOI: 10.1116/1.577729
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-induced interfacial oxidation of chromium on polyimide

Abstract: Interfacial strength of Cr/polyimide thin film structures and its durability to thermal exposure as a function of process variables was determined by 90° peel testing. Results were correlated with surface and interfacial characterization of thin film structures and peel failure surfaces using Auger, x-ray photoelectron spectroscopy, and secondary ion mass spectroscopy techniques. Initial adhesion in as-deposited Cr/polyimide structures exhibits a mild dependence on radio-frequency Ar plasma surface modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…TEM microscopy showed no evidence of grain growth of the electroplated Cu films during annealing process. Even annealed in N2 atmosphere, it has been reported that interfacial fracture energy of Cr/PI was reduced due to the formation of Cr oxide at the Cr/PI interface and thermal expansion mismatch between polyimide and metal films [16][17][18]. Comparing to specimens which were not annealed, both interfacial fracture energy and mechanical properties of Cu/Cr films were changed with first annealing process.…”
Section: Resultsmentioning
confidence: 76%
“…TEM microscopy showed no evidence of grain growth of the electroplated Cu films during annealing process. Even annealed in N2 atmosphere, it has been reported that interfacial fracture energy of Cr/PI was reduced due to the formation of Cr oxide at the Cr/PI interface and thermal expansion mismatch between polyimide and metal films [16][17][18]. Comparing to specimens which were not annealed, both interfacial fracture energy and mechanical properties of Cu/Cr films were changed with first annealing process.…”
Section: Resultsmentioning
confidence: 76%
“…The aforementioned methods, however, have limitations. For example, ion bombardment may thermally degrade the substrate [24], while the Cr interlayer is prone to oxidization [24,25], both leading to reduced interfacial adhesion and ductility of the film/substrate system. It is therefore important to explore new techniques for enhanced interfacial adhesion and ductility of polymer-supported metal films.…”
Section: Introductionmentioning
confidence: 99%
“…1 Because polyimides are the most extensively used polymer in microelectronic industries, numerous studies have been conducted to solve polyimides' adhesion problems. Approaches to improve polyimides' adhesion include adding flexible structure into the polyimide backbone, 2 wet chemistry treating the surface of polyimide to reform polyamic acid, 3 partial curing 4 or solvent swelling the polyimide, 5 plasma activating the surface, 6 using Cr as adhesion promoter, 7 and applying adhesive, 8 etc. Most approaches were developed to solve specific interface problems involved with the sequential processing of polyimides.…”
Section: Introductionmentioning
confidence: 99%